Penerapan Mobilisasi Progresif Terhadap Perubahan Tekanan Darah Pada Pasien Stroke Di Ruang Icu - Linda Nuryanti; Endang Supriyanti (Journal of Community Service and Engagement, 2026)
This study aimed to analyze the effect of progressive mobilization on blood pressure changes in stroke patients admitted to the intensive care unit of RSUD Limpung. An empirical case study design with a one-group pretest–posttest approach was applied to five patients who met the inclusion criteria of hemodynamic stability and clinical eligibility for mobilization. Blood pressure was measured using a non-invasive method before and after a structured progressive mobilization intervention consisting of head elevation, range of motion exercises, and gradual activity adjustment based on patient tolerance. The findings demonstrated a consistent reduction in systolic and diastolic blood pressure across all participants, indicating a positive physiological response to the intervention. The magnitude of change suggested clinically relevant improvements in hemodynamic stability rather than absolute normalization. Mechanistically, progressive mobilization supports cardiovascular adaptation, enhances circulation, and optimizes autonomic regulation. These findings highlight the clinical relevance of progressive mobilization as a safe and evidence-based nursing intervention in intensive care settings, contributing to improved patient outcomes and supporting comprehensive stroke management strategies.